Implementasi statistika sebagai alat analisis dalam pengambilan keputusan di bidang pendidikan - Jerhi Wahyu Fernanda; Noer Hidayah (University of Islam Malang, 2021)
Statistics is a part of mathematics lessons in senior high school XII classes as well as mathematics specialization class XII. A comprehensive understanding of the basic concepts of statistics is needed to convey the material in class. The results of the discussion with the Mathematics MGMP of Kediri City, a workshop is needed to deepen the understanding of mathematics teachers, especially in the material of normal distribution and binomial distribution. In addition, Material about item analysis and standard setting is need to be introduced. Both materials can be used in evaluating learning. The workshop was held in two days. The first workshop held on 4 November 2020. Material for this day was normal distribution. At the end of the activity on this date, participants were given practice questions that should to be uploaded on google classroom. Second workshop held on 17 November 2020. Participatn are given material about binomial distribution, item analysis, and standard setting. This workshop has increased the level of understanding of participants on the material of binomial distribution and normal distribution. The increase in understanding is measured by the evaluation of the answers to the practice questions collected by the participants and the evaluation of the resource persons during the workshop activity. The next workshop can be conducted with the theme of statistical inferential analysis in educational research. The statistical analysis is very helpful for educators to analyze research data in education.